Analisis Pengaruh Penggunaan Kata Anjay terhadap Kondisi Psikis Generasi-Z - M. Ichsan Nawawi; Risnawati Ibnas; Mahda Al Maidah; Wa Ode Firda Sasmita Darwin; St. Hasna Nurfitriani; Riska Amalia; Mitra Aulia Ramli; Deni Candra (Universitas Al Azhar Indonesia, 2022)
Abstract – The word